2014
DOI: 10.1186/1743-422x-11-72
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of human hepatitis E virus from Italy: comparative analysis of five reverse transcription-PCR assays

Abstract: BackgroundHepatitis E (HEV) is an important public-health concern as a major cause of enterically transmitted hepatitis worldwide. In industrialised countries it is considered rare, and largely confined to travellers returning from endemic areas. However, autochthonous (locally acquired) HEV infection is also emerging in these regions. The infection is caused by different genotypes, depending on whether it is travel-related or autochthonous. Conventional RT-PCR followed by sequencing of PCR products can identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Previous studies reported that quantitative HEV-specific real-time RT-PCR of a conserved region (ORF2/ORF3) in the HEV genome is the most sensitive method for HEV RNA detection (25). On the other hand, consensus nested RT-PCRs for the amplification of longer fragments (Ͼ300 nt) located in different HEV genome regions (ORF1 and ORF2) are useful for molecular characterization and genotyping/subtyping of HEV variants (38). However, full-length genome sequencing is definitely mandatory for proposing new HEV variants (genotype and subtype).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that quantitative HEV-specific real-time RT-PCR of a conserved region (ORF2/ORF3) in the HEV genome is the most sensitive method for HEV RNA detection (25). On the other hand, consensus nested RT-PCRs for the amplification of longer fragments (Ͼ300 nt) located in different HEV genome regions (ORF1 and ORF2) are useful for molecular characterization and genotyping/subtyping of HEV variants (38). However, full-length genome sequencing is definitely mandatory for proposing new HEV variants (genotype and subtype).…”
Section: Discussionmentioning
confidence: 99%
“…However, failure to sequence HEV appear to be common, for example in a study, where only 9/16 (56%) and 3/9 (33%) of qPCR HEV-positive samples from wild boar and red deer could be sequenced after nested-PCR amplification [ 46 ]. In another study it was demonstrated that conventional PCR assays targeting different regions of the HEV genome could only detect a proportion of HEV positive (as demonstrated by serology and qPCR) reference samples [ 47 ]. This could be due to genetic variability of the strains, thereby explaining why highly similar moose RdRp sequences showed a similar ability to be sequenced in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nested PCRs targeting HEV open reading frame 1 (ORF1; 133 nucleotides) and the ORF2/3 junction (97 nucleotides) were then performed separately using Phusion high-fidelity DNA polymerase (Thermo Fisher, USA)/Titanium Taq DNA polymerase (TaKaRa, Japan). Primers used are listed in Table S2 (47). Precautionary measures to minimize cross-contamination were implemented: (i) master mix preparation, DNA/RNA template addition, thermocycling, and post-PCR steps (e.g., gel electrophoresis) were performed in four separate rooms, and (ii) filtered pipette tips were used.…”
Section: Methodsmentioning
confidence: 99%